Estimates of evapotranspiration with PROBA-V images in a crop field on the coast of Hermosillo, Sonora, Mexico. - Saiz Rodríguez, Ramón; Aguirre López, Génesis Luisana; Rodríguez, Julio Cesar; Watts Thorp, Christopher John; Saiz Rodríguez, Juan Alejandro; Ochoa Granillo, Alfredo; Saiz Hernández, Juan Arcadio (REVISTA TERRA LATINOAMERICANA, 2017)
Evapotranspiration is one of the most important hydrological cycle processes in balance and water availability studies in a crop field of the arid region of northwestern Mexico. In this work, images of the Normalized Difference Vegetation Index (NDVI) obtained from the PROBA-V satellite were used to develop a model to estimate the evapotranspiration (ET) in a watermelon crop in an agricultural area of the coast of Hermosillo, Sonora. The procedure was based on the correlation between the crop coefficient (Kc) and the NDVI value. With the developed model, the ET of a watermelon crop was estimated and the results were contrasted with ET values measured with the eddy covariance method. The correlation between the measured values and the estimated values was r2 = 0.729 and, although the results were acceptable, they can improve as the number of good quality satellite images increases and ET is measured in a greater variety of agricultural crops.